Analisis Yuridis Pembatalan Akta Hibah Tanah Oleh Pengadilan Negeri Kupang (Studi Kasus Putusan Nomor 298/PDT.G/2021/PN/KUPANG) - Neonufa, Ananda Pricely Rindang; Mauritsius, Darius; Dinata, Husni Kusuma (Artemis Law Journal, 2025)
Cancellation of a deed of gift has legal consequences that the assets that have been donated must be returned to the grantor, as regulated in Articles 1673 and 1674 of the Civil Code. The problem in this study is how are the considerations of the parties in the decision of the Case Study of Decision Number 298/pdt.g/2021/PN/Kupang? And how are the considerations of the judge in the decision of the Case Study of Decision Number 298/pdt.g/2021/PN/Kupang? The type of research used is normative legal research by collecting, reading, tracing a number of library materials and analyzing Decision Number 298/pdt.g/2021/PN/Kupang. The results of this study show: (1) The considerations of the parties in this case the Plaintiff, Defendant and Co-Defendant I and Co-Defendant II each have strong reasons regarding their involvement in the land grant process until the issuance of the certificate, but from all the reasons put forward there are several irregularities that weaken the Defendant and Co-Defendant and (2) the basis for the judge's considerations in this decision is in accordance with the objectives of the law, namely Justice, Certainty and Benefit. Legal certainty has occurred after the deed of grant was issued in the name of the defendant, but the judge set aside the objective of legal certainty, but in this case the judge also took another objective, namely justice.